The safety and effectiveness of 2-liter polyethylene glycol plus ascorbic acid in patients with liver cirrhosis: A retrospective observational study. Issue 51 (December 2017) - Lee, Jae Min; Lee, Jae Hyung; Kim, Eun Sun; Lee, Jung Min; Yoo, In Kyung; Kim, Seung Han; Choi, Hyuk Soon; Keum, Bora; Seo, Yeon Seok; Jeen, Yoon Tae; Lee, Hong Sik; Chun, Hoon Jai; et al.
Abstract : Abstract: The safety of bowel-cleansing agents is an important issue in clinical practice, especially in patients with chronic diseases. Although the safety and efficacy of polyethylene glycol (PEG) has been investigated in many studies, few studies on PEG plus ascorbic acid exist. In this study, we compared the safety of 2 bowel-cleansing agents for patients with liver cirrhosis: 2-liter PEG (2 L PEG) plus ascorbic acid versus 4-liter PEG (4 L PEG). We performed a retrospective study on colonoscopy in patients with liver cirrhosis. Patients referred for colonoscopy were divided into 2 groups: 2 L PEG plus ascorbic acid (n = 105) and 4 L PEG (n = 61). Safety was assessed by comparing the clinical factors and laboratory findings as follows: blood biochemistry, electrolytes, weight change, and bowel-cleansing quality. Serum electrolytes, laboratory findings, and body weight showed no significant change between the 2 groups. There was no significant change in clinical factors before and after bowel preparation in the PEG group or the PEG plus ascorbic acid group. The acceptability and compliance of patients was better in the 2 L PEG plus ascorbic acid than the 4 L PEG group. In subgroup analysis, patients with compensated or decompensated cirrhosis showed no increased risk of electrolyte imbalances after bowel preparation. Child–Pugh scores did not influence the outcome after bowel cleansing. Successful cleansing was mostly achieved in both groups. Our analysis showed that of the use of 2 L PEG plus ascorbic acid could be a safe choice for colonoscopy in patients with liver cirrhosis.